A ReaxFF molecular dynamics study on the mechanism and the typical pyrolysis gases in the pyrolysis process of Longkou oil shale kerogen. Issue 15 (12th October 2020) - Zhang, Zhijun; Guo, Liting; Zhang, Hanyu
ABSTRACT: The combination of Reactive molecular dynamics (RMD) simulations and a reactive force field (ReaxFF) was employed to investigate the chemical mechanisms and product distribution in the process of oil shale kerogen pyrolysis. A large-scale reactive system based on five structural models used in the simulation was constructed according to the analysis results of a series of detection about kerogen extracted from Longkou oil shale to investigate the reaction processes of oil shale. The characteristics observed in the simulation agree well with the known characteristics of the oil shale structure and reactions. The simulation results proved the importance of temperature exert on the product distributions, intermolecular interactions and elementary reactions in the process of pyrolysis. A conclusion was made about the suitable temperature range for producing useful organic gases and the highest yield of shale oil. The detailed chemical reaction process of Longkou oil shale pyrolysis was described in this work as well. This work is an intensive study on the pyrolysis mechanism and the formative path of the typical products especially shale gases at different temperatures at the atomic level and will be of great significance for the development and utilisation of oil shale mineral resources.